Transapical off-pump mitral valve repair with Neochord implantation: Early clinical results. (1st February 2016) - Colli, Andrea; Manzan, Erica; Zucchetta, Fabio; Bizzotto, Eleonora; Besola, Laura; Bagozzi, Lorenzo; Bellu, Roberto; Sarais, Cristiano; Pittarello, Demetrio; Gerosa, Gino
Abstract: Background: This prospective study aims to assess early clinical outcomes in patients undergoing Transapical Off-Pump Mitral Valve Intervention with Neochord Implantation (TOP-MINI). Methods and results: Forty-nine patients with severe symptomatic degenerative mitral regurgitation (MR) were treated. Median age was 72 years (IQR 58-78) and median Euroscore-I was 3.26% (IQR 0.88–8.15). Forty-four patients (89.8%) presented with posterior leaflet prolapse (LP), 4 (8.2%) with anterior LP and 1 (2%) with combined disease. Acute procedure success (defined as successful placement of at least 3 neochords with reduction of residual MR to less than 2 +) was achieved in all patients. In-hospital mortality was 2%. At 30 days major adverse events included one AMI (2%) successfully treated percutaneously and one sepsis (2%), no stroke or bleeding events occurred. At 3 months overall survival was 98%. MR was absent in 16 patients (33.4%), was grade 1 + in 15 (31.2%), and was grade 2 + in 12 (25%). Five patients (10.4%) developed recurrent severe MR due to anterior native chordae rupture. Four of them were successfully re-operated. At 3 months follow-up freedom from reoperation was 91.7 ± 4%. Conclusions: Early results with Neochord procedure indicate that TOP-MINI is feasible and safe. Efficacy is maintained up to 3 months follow-up with significant clinical benefit for the patients.